Gen Z dan Perilaku Konsumsi Konten Influencer pada TikTok - Arina Himatul Husna; Desy Mairita (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2024)
Digital marketing grows as increasingly usage of the internet in society. Moreover, social media has changed the new landscape of marketing. Marketing through influencers was considered to be an effective marketing technique. That is also on TikTok App. Young users in 13-27 years old, known as Gen Z, always involve influencers in their digital activities. This research reviews how Gen Z's behavior in accessing Influencer content that was mentioned some brand. How these users make consuming content decisions through persuasion communication created through influencer content on tiktok. This research uses a phenomenological approach that is analyzed with the concept of Elaboration Likelihood Model (ELM). The result showes that there is a dichotomy of gen Z behavior in consuming influencer content. On the central route, Gen Z users follow content if the influencer's brand-related story aligns with their values and beliefs. Then understanding the product message emphasizes understanding the features, advantages, and disadvantages of the product before deciding on a particular behavior. Meanwhile, on the peripheral route, Gen Z users prefer visually and aesthetically attractive content before following influencer content. The product being communicated is adopted if it is considered popular or follows the short-term benefits offered.